Program Qur’an Camp dalam Penguatan Kecintaan Al Qur’an pada Anak di Sekolah Alam Perwira Purbalingga - Muhammad Hananika Anugerah Yusuf; Muh. Hizbul Muflihin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This article describes the Qur'an camp program, its methods, and the love of the Qur'an by children. The program is motivated by the declining interest in reading students or children towards the Qur'an. Therefore, this program has several objectives, including motivating children to improve with the Qur'an and broadcasting to learn the Qur'an. This article is a research that uses data reduction analysis techniques, data presentation, and data levers, with data collection techniques of observation, interviews, and documentation called qualitative research. This research resulted in several concepts in the Qur'an Camp Program, namely first, the emergence of the desire of students and coaches to be able to train themselves and have useful knowledge (amal Jariyah) so that children can love the Qur'an. second, the founders of the foundation have some relatively similar experiences with qur'an activities in educational institutions. Furthermore, regarding the process of activities from this program carried out in certain months or routinely every month of Ramadan. This program has the advantage of memorizing with hand movements. Followed by supporting activities such as memorization deposits, congregational prayers, evening prayers, motivational materials, bonfires, cheerful tales of hafidz qur'an.